Réflexion sur l’utilisation de groupes de discussion comme outil de documentation du savoir écologique traditionnel - Nancy Tanguay (VertigO, 2010)
Prior to the consideration and integration of traditional ecological knowledge, documentation is required. One of the most established semi-directed interview method to achieve this task is through focus groups. Many procedural aspects of this method have been discussed in the literature. However, few authors have addressed the additional challenges posed by conducting focus groups within an aboriginal community. The purpose of this paper is to examine these issues throughout the different stages of documenting traditional ecological knowledge, including the input of four focus groups conducted in two Atikamekw communities in Quebec, Canada. It is important to take into account the cultural context when conducting focus groups in order to tailor the research stages, primarily the analysis.